Study of binary self-assembled monolayers of a novel anchoring thiol (11-mercaptoundecyl-N′,N″,N‴-trimethylammonium) in the electron transfer with glucose oxidase enzyme - Baldo, Thaísa A. [UNESP]; David-Parra, Diego N.; Gomes, Homero M. [UNESP]; Seraphim, Patrícia M. [UNESP]; Teixeira, Marcos F.S. [UNESP] (Elsevier, 2018)
In this study, we explore the fabrication and properties of a sensing electrochemical platform that is based on a novel 11-mercaptoundecyl-N′,N″,N‴-trimethylammonium hexacyanoferrate (MAH) and 6-(ferrocenyl)hexanethiol (FT)/glucose oxidase (GOx) on gold substrate. The hexacyanoferrate and ferrocene moieties that were immobilized on the gold surface were examined as electron transfer mediators with the oxidase glucose. The sensing platform, based on 11-mercaptoundecyl-N′,N″,N‴-trimethylammonium hexacyanoferrate (MAH) and 6-(ferrocenyl)hexanethiol (FT)/GOx modified gold electrode, shows the potential to work with two distinct mechanisms for electrochemical response. The hexacyanoferrate anion that was anchored at positive edge charge of the 11-mercaptoundecyl-N′,N″,N‴-trimethylammonium on the gold surface provided an efficient electron transfer. It was demonstrated that in the design of the GOx/MAH, the FT/Au electrode is facilitating the electron transfer from GOx toward the gold substrate. We believe that this study adds a new facet to nanobioelectronics with applications for biofuels and sensorial platforms.
Keywords: Electrocatalysis; Self-assembled monolayer; Sensorial platform; Tafel-Marcus